Chernobyl roulette : a war story - Plokhy, Serhii (2024)
"On 24 February 2022, the first day of Russia's full-scale invasion of Ukraine, armoured vehicles approached the Chernobyl nuclear power plant in northern Ukraine. It was the most direct way for them to reach the capital - and an extraordinarily reckless plan after the disaster that had taken place there three decades earlier. Russian occupation of the plant had begun. It would last thirty-five days. Closely reported and narrated from multiple perspectives, this is the story of the Ukrainians who were held hostage and worked shifts for weeks instead of days to spare the world a new nuclear accident. We meet Valentyn Heiko, the foreman who had also been there for the clean-up of the Chernobyl accident in 1986 and turned sixty during the occupation; plant workers who found a way to celebrate International Women's Day despite all odds; Russian officers who had no knowledge of nuclear reactors; and four stalkers who were caught in the middle and stood in for the overworked cook"–Amazon